Human development theories windows on culture - Thomas, R. Murray (Robert Murray) 1921- (Thousand Oaks, California London SAGE, 1999)
Human Development Theories reveals how different theories of development contribute to an understanding of cultural influences on the lives of children and youth
Title from title screen (viewed October 20, 2023)
Includes bibliographical references and index
Specialized
Description based on print version record
Keywords: Child development; Cognition and culture; Developmental psychology; Socialization